2019
DOI: 10.1111/jcmm.14227
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical effects of CRT promoting autophagy via mitochondrial calcium uniporter down‐regulation and mitochondrial dynamics alteration

Abstract: The mechanism of cardiac resynchronization therapy ( CRT ) remains unclear. In this study, mitochondria calcium uniporter ( MCU ), dynamin‐related protein‐1 ( DNM 1L/Drp1) and their relationship with autophagy in heart failure ( HF ) and CRT are investigated. Thirteen male beagle's dogs were divided into three groups (sham, HF , CRT ). Animals received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“… 177–180 The effect of cardiac resynchronization to effect reverse remodelling is accompanied by activation of autophagic flux and improvement in mitochondrial function. 181 Therefore, currently available treatments for heart failure appear to exert a consistently favourable influence on the interplay of SIRT1/AMPK and Akt/mTOR in a manner that promotes autophagy.…”
Section: Importance Of Longevity Gene Signalling and Autophagy Modulamentioning
confidence: 99%
“… 177–180 The effect of cardiac resynchronization to effect reverse remodelling is accompanied by activation of autophagic flux and improvement in mitochondrial function. 181 Therefore, currently available treatments for heart failure appear to exert a consistently favourable influence on the interplay of SIRT1/AMPK and Akt/mTOR in a manner that promotes autophagy.…”
Section: Importance Of Longevity Gene Signalling and Autophagy Modulamentioning
confidence: 99%
“…PINK/Parkin can mediate mitophagy during MI. It has been found that cardiac resynchronization therapy following heart failure caused by MI and berberine, which belongs to the traditional Chinese medicine, can all induce an increase in PINK/Parkin expression and mitophagy 107,108 . Yao et al 80 found that an injection of hydrogen‐rich saline can attenuate inflammation and apoptosis of the damaged myocardium by enhancing mitophagy.…”
Section: Mitophagy Of Cardiomyocytesmentioning
confidence: 99%
“…It has been found that cardiac resynchronization therapy following heart failure caused by MI and berberine, which belongs to the traditional Chinese medicine, can all induce an increase in PINK/Parkin expression and mitophagy. 107,108 Yao et al 80 found that an injection of hydrogen-rich saline can attenuate inflammation and apoptosis of the damaged myocardium by enhancing mitophagy. The authors further found that after knocking out the PINK gene, the protective effect of hydrogen was partially reversed, suggesting that hydrogen can enhance PINK/Parkin-mediated mitophagy to attenuate MI.…”
Section: Application In MI Therapiesmentioning
confidence: 99%
“…Interestingly, pharmacological inhibition of mtCU restores the levels of autophagy and mitophagy, partially prevents both the cardiomyocytes hypertrophy and myocardial fibrosis, and alleviates the concomitant ventricular asynchrony [103]. On the other hand, correction of cardiac dysfunction by cardiac resynchronization therapy provides mitochondrial fission and autophagosome/mitophagosome formation underlying the alleviated cell enlargement and myocardial fibrosis [124]. This therapeutic approach leads to a significant reduction in MCU and p62 content accompanied by DRP1 upregulation [124], which brings up an important question of mtCU participation in the mitochondria quality control.…”
Section: The Role Of Mtcu In Cardiac Musclementioning
confidence: 99%
“…On the other hand, correction of cardiac dysfunction by cardiac resynchronization therapy provides mitochondrial fission and autophagosome/mitophagosome formation underlying the alleviated cell enlargement and myocardial fibrosis [124]. This therapeutic approach leads to a significant reduction in MCU and p62 content accompanied by DRP1 upregulation [124], which brings up an important question of mtCU participation in the mitochondria quality control. Cho et al have recently reported that mtCU mediates the DRP1-dependent Zn 2+ influx into the mitochondrial intermembrane space during fission [125].…”
Section: The Role Of Mtcu In Cardiac Musclementioning
confidence: 99%